Role of CRISPR-Cas9 in Understanding, Modelling, and Treating Cancer - Mannan, Abdul; Javaid, Iqra; Khan, Mariam; Akhtar, Junaid; Farooq, Aroosa; Javaid, Rabia Basri; Javed, Ayesha; Danish, Muhammad (Indus Journal of Bioscience Research, 2025)
Background: Cancer is a genetic disease resulting from cumulative genetic/epigenetic aberrations. The genome editing technique known as Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR)-Cas9 has been widely used for effective gene disruption and modification in a variety of cell types and organisms, both in vitro and in vivo. Cancer treatment using CRISPR-Cas9 has showed a lot of promise. Objective: To synthesize current knowledge on the understanding, modeling and treatment of Cancer through CRISPR-Cas9 technique. To delineate about the role of CRISPR-Cas9 in understanding, modeling and treating cancer. Cancer disease, explore the genetic and environmental factors contributing to it, and assess the potential of novel therapeutic approaches like CRISPR-Cas9 towards it. Methods: A narrative review was conducted through a structured search of PubMed, Scopus, Web of Science, and Google Scholar, focusing on articles published on role of CRISPR-Cas9 on cancer. Keywords related to CRISPR-Cas9 and its implications across cancer were used to identify relevant studies. Inclusion criteria targeted original research, reviews, and meta-analyses published in English that contributed to CRISPR-CAS9 role in cancer understanding, modeling and treatment. Data extraction and synthesis were performed to highlight key findings, mechanisms, and therapeutic strategies. Results: The review emphasizes the critical role of CRISPR-Cas9 in understanding, modeling and treatment of cancer in the wide range. It identifies CRISPR-Cas9 contributing to the treatment of cancer and highlights it has very important role in treating it. Additionally, the review explores emerging therapies. Conclusion: The genetic mutations and environmental influences contributing to the cancer and progression. CRISPR-Cas9 has a pivotal role in the treatment of cancer. Understanding the complex mechanisms and working for proper treatment of cancer through it is very essential for devising effective treatment. While significant advances have been made, further research is needed to fully exploit the therapeutic potential of targeting cancer through a gene editing tool like CRISPR-Cas9.